2016
DOI: 10.2147/ppa.s98498
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes after methylphenidate in adults with attention-deficit/hyperactivity disorder treated with lisdexamfetamine dimesylate or atomoxetine

Abstract: PurposeTo compare treatment adherence, discontinuation, add-on, and daily average consumption (DACON) among adults with attention-deficit/hyperactivity disorder receiving second-line lisdexamfetamine dimesylate (LDX) or atomoxetine (ATX), following methylphenidate.Patients and methodsA retrospective cohort study using US commercial claims databases (Q2/2009–Q3/2013).ResultsAt month 12, the LDX cohort (N=2,718) had a higher adherence level (proportion of days covered: 0.48 versus 0.30, P<0.001) and was less lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
(58 reference statements)
0
3
1
1
Order By: Relevance
“…In an earlier (United States) study, the rate of discontinuation in adults was within the range observed in the present study, despite a shorter study duration (1 year). Discontinuation of LDX in the present study was somewhat lower than that reported for ATX ( Joseph et al 2016), whereas in another 1-year (United States) study, discontinuation of MPH in children was within the range seen in the present study (Faraone et al 2007).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In an earlier (United States) study, the rate of discontinuation in adults was within the range observed in the present study, despite a shorter study duration (1 year). Discontinuation of LDX in the present study was somewhat lower than that reported for ATX ( Joseph et al 2016), whereas in another 1-year (United States) study, discontinuation of MPH in children was within the range seen in the present study (Faraone et al 2007).…”
Section: Discussioncontrasting
confidence: 58%
“…In a recent 3-year study in adults in France, the calculated average daily dose of MPH exceeded the maximum approved dose according to European labels (Pauly et al 2018). Two United States studies have shown that the calculated daily average consumption, relative to the prescribed dose, is generally lower for LDX than for OROS-MPH, MAS XR, or ATX (Hodgkins et al 2012 ; Joseph et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study using US commercial claims databases compared 3,392 patients who discontinued methylphenidate and started either lisdexamfetamine or atomoxetine as second-line treatments. The study found that patients treated with lisdexamfetamine had higher treatment adherence and lower discontinuation rates as compared to those treated with atomoxetine [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that due to its pharmacokinetic profile, lisdexamfetamine has a lower abuse-related drug-liking score compared to immediate-release dextroamphetamine [ 17 ]. In addition, various studies have demonstrated the efficacy of lisdexamfetamine in the treatment of adults with ADHD [ 14 , 15 , 18 ]. Additionally, lisdexamfetamine may be effective in the treatment of stimulant (methamphetamine) use disorder [ 4 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…La alta y prolongada eficacia, medida a través de parámetros clínicos de síntomas cardinales del TDAH, de afectación del funcionamiento cotidiano, calidad de vida y neuropsicológicos, así como la facilidad de administración y, por tanto, la adhesión terapéutica, el rápido comienzo de acción y el buen perfil de seguridad, configuran la LDX como un tratamiento completo y efectivo [7,19,21,39], con una satisfactoria relación coste-efectividad [27,44,45].…”
Section: Acción Efectiva Aproximadaunclassified